Strategi Mempertahankan Bisnis Wisata Sawah Lega Hegar Resort Garut dengan Metode Competitive Positioning Analysis - Dian Kusma Noria; Hilmi Aulawi (Institut Teknologi Garut, 2022)
Sawah Lega Hegar Resort is one of the natural attractions located in Garut Regency, precisely in Maripari Village, Sukawening District, Garut Regency. The purpose of this research is to find out the location of the company in the competitor's market and determine a strategy so that the company can compete and maintain the business that has been built. Data collection was carried out through direct observation and interviews with employees of Sawah Lega Hegar Resort Garut. The research was conducted using the Competitive Positioning Analysis method, there are 3 steps that must be taken to carry out the CPA method, including identifying the company's strategic and market focus using STP (Segmenting, Targeting, Positioning), building analysis using the 8P marketing mix (product, price, promotion). , place, people, physical evidence, process, productivity and quality) and reviewing results and formulating strategies using the SWOT analysis method. The results of the SWOT Quadrant are the company's position in the market and the SWOT matrix is ​​the strategy that the company must implement. Based on the results of the SWOT analysis conducted, the company is located in Quadrant 2 with an analysis of overcoming threats with strengths. That is, even though there are many threats that arise, the company still has superior strengths compared to its weaknesses. This is the analysis of the SWOT matrix which formulates a strategy based on the Strength, Weakness, Opportunity and Threats variables. The formulation of the Strategy resulted in 4 sell strategies in a nutshell, namely Utilizing and maintaining functional areas, lodging facilities, distinctive natural nuances and good product quality by increasing selfie photo spots, children's rides and attractive promotions to meet market demand. This is done to avoid threats and take advantage of opportunities such as events that are becoming popular, people who need holidays and the trend of nature tourism. So that the increase in several useful facilities to support events or other consumer needs.